2014
DOI: 10.1177/0969733014557135
|View full text |Cite
|
Sign up to set email alerts
|

Values in nursing students and professionals

Abstract: This study shows intergenerational change in personal values among both nursing students and young nursing professionals. Findings suggest the need to pay more attention to value training and professional socialization during the schooling period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
1
31
0
1
Order By: Relevance
“…This system of values and beliefs is reflected by the way nursing care is provided, and may be influenced by social, cultural and/or political factors. These values can be modified through educational, clinical and personal experience (Jiménez‐López et al ; Parandeh et al ). Universities must play a key role in the adoption of these values (Kantek et al ; Kaya et al ).…”
Section: Introductionmentioning
confidence: 99%
“…This system of values and beliefs is reflected by the way nursing care is provided, and may be influenced by social, cultural and/or political factors. These values can be modified through educational, clinical and personal experience (Jiménez‐López et al ; Parandeh et al ). Universities must play a key role in the adoption of these values (Kantek et al ; Kaya et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Bentzen et al (2013) reported that nurses understood that ethical values are of critical significance for the quality of care in the nursing profession. Several researchers have recognized the significance of ethical values, highlighting that professional values symbolize the fundamental beliefs of what is right, good or desirable (Cetinkaya-Uslusoy et al 2015;Gallegos & Sortedahl 2015;Jimenez-Lopez et al 2014;LeDUC & Kotzer 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similar data was obtained by Lewicka et al [23] in a group of nursing and midwifery students. A Spanish study conducted with a group of 589 nurses and 2,295 students of nursing has shown that health ranks fifth among the values advocated by working nurses, and third with nurs-ing students [18]. Different results had obtained Rassin [24] in the study on personal and professional values among Israeli nurses, for whom values such as respect for personal dignity, altruism and trust, honesty, responsibility and reliability were indicated as a manifestation of motivation and personal attitude, influencing the realization of the professional role.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, studies on the hierarchy of values among nurses or nursing students, indicating the position they tend to attribute to health as a part of their hierarchy of values, are rather rare [17]. International research lean towards focusing on analyzing the axiological system followed by nurses, based on the profession they perform and related decision-making process [18]. Therefore, our and the participants were offered the option to withdraw their consent to participate in the study at any time.…”
Section: Introductionmentioning
confidence: 99%